2008
DOI: 10.1523/jneurosci.3410-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Is a Functional Component of the Autonomous Circadian System in the Suprachiasmatic Nucleus

Abstract: The suprachiasmatic nucleus (SCN) is the master circadian pacemaker driving behavioral and physiological rhythms in mammals. Circadian activation of mitogen-activated protein kinase [MAPK; also known as ERK (extracellular signal-regulated kinase)] is observed in vivo in the SCN under constant darkness, although the biological significance of this remains unclear. To elucidate this question, we first examined whether MAPK was autonomously activated in ex vivo SCN slices. Moreover, we investigated the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…It is tempting to speculate that the circadian phenotype of the PHLPP1-null mice described here could be parallel to the function of PHLPP1 in memory formation. This intriguing possibility is supported by the fact that PKC and MAPKs are important for circadian function (22,23) and that PHLPP1 itself oscillates in the SCN (11). Our findings support a scenario in which PHLPP1 may operate in controlling the consolidation of circadian periodicity after resetting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tempting to speculate that the circadian phenotype of the PHLPP1-null mice described here could be parallel to the function of PHLPP1 in memory formation. This intriguing possibility is supported by the fact that PKC and MAPKs are important for circadian function (22,23) and that PHLPP1 itself oscillates in the SCN (11). Our findings support a scenario in which PHLPP1 may operate in controlling the consolidation of circadian periodicity after resetting.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps PHLPP1 may also regulate the phosphorylation state of some circadian regulators, including CLOCK and PER2, the phosphorylation of which has been shown to be critical for normal circadian function (31,32). Furthermore, PKC and MAPK, (PHLPP1-regulated kinases) have been shown to be important for clock resetting (22,23). Future studies will establish whether PHLPP1 physiologically dephosphorylates any components of the clock machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that circadian activation of ERK is autonomously regulated in the suprachiasmatic nuclei (SCN), the central circadian pacemaker in mammals. 22,23) This finding, together with our previous observation that ERK mediates light-induction of zCry1a expression, 11) suggests that ERK signaling cascade could also contribute to the transcriptional regulation of zCry1a gene in DD conditions. In order to address this, we first tested the temporal pattern of ERK phosphorylation in zebrafish cultured cells.…”
Section: Fig 3 Effects Of Zclock3-deltac On Transcription Of Zcry1amentioning
confidence: 56%
“…Indeed, circadian changes of phosphorylation and dephosphorylation of kinases have been reported in cyanobacteria and mammals. 23,25,26) It is therefore conceivable that an orchestrated temporal program of protein phosphorylation contributing to control a proper 24-h clockwork may exist in zebrafish as well. Such a program would require the activity of kinases and, necessarily, phosphatases.…”
Section: Fig 3 Effects Of Zclock3-deltac On Transcription Of Zcry1amentioning
confidence: 99%
“…Yamaguchi et al 35 and Welsh et al 4,5 pioneered real-time bioluminescence imaging by integrating a specially designed microscope with a highly sensitive, low-noise CCD camera 15 to achieve single cell resolution. In recent years, more sensitive imaging systems have become commercially available, including LV200 (Olympus) and CellGraph (AB3000-B, Atto) with an ultrasensitive cooled and back-illuminated electron multiplying CCD and multicolor filters 36,37 . Imaging has also been used in more sophisticated HTS experiments, e.g., a ViewLux CCD imager (Perkin-Elmer) combined with the GNF automated robotic system (GNF Systems).…”
Section: Recording Devices and Throughput Considerationsmentioning
confidence: 99%